2011
DOI: 10.1371/journal.pone.0027648
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-Processing Enzyme Dicer Is Essential for Thyroid Function

Abstract: Dicer is a type III ribonuclease required for the biogenesis of microRNAs (miRNAs), a class of small non-coding RNAs regulating gene expression at the post-transcriptional level. To explore the functional role of miRNAs in thyroid gland function, we generated a thyrocyte-specific Dicer conditional knockout mouse. Here we show that development and early differentiation of the thyroid gland are not affected by the absence of Dicer, while severe hypothyroidism gradually develops after birth, leading to reduced bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 33 publications
(38 reference statements)
1
43
0
Order By: Relevance
“…In addition, Dicer is an important ribonuclease involved in the biogenesis of miRNAs (154). Frezzetti et al reported that the development of the thyroid gland was not affected by the absence of Dicer through using thyrocyte-specific Dicer knockout mice, but Dicer knockout resulted in severe hypothyroidism (155). In addition, Dicer inactivation also increased the expressions of Tg and decreased the expressions of cell adhesion proteins in the thyroid cells, such as Cdh16 and Cdh1 (155).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dicer is an important ribonuclease involved in the biogenesis of miRNAs (154). Frezzetti et al reported that the development of the thyroid gland was not affected by the absence of Dicer through using thyrocyte-specific Dicer knockout mice, but Dicer knockout resulted in severe hypothyroidism (155). In addition, Dicer inactivation also increased the expressions of Tg and decreased the expressions of cell adhesion proteins in the thyroid cells, such as Cdh16 and Cdh1 (155).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
“…Frezzetti et al reported that the development of the thyroid gland was not affected by the absence of Dicer through using thyrocyte-specific Dicer knockout mice, but Dicer knockout resulted in severe hypothyroidism (155). In addition, Dicer inactivation also increased the expressions of Tg and decreased the expressions of cell adhesion proteins in the thyroid cells, such as Cdh16 and Cdh1 (155). Saeki et al found that AITD patients had lower expression of Dicer and DROSHA compared with healthy controls, and DICER rs1057035 and DROSHA rs644236 were obviously associated with susceptibility to GD (156).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
“…After that, they are exported by exportin-5 to the cytoplasm Marini et al, 2011). In the cytoplasm, pre-miRNAs undergo further processing by endonuclease Dicer and become mature miRNAs Frezzetti et al, 2011a;Marini et al, 2011). Mature miRNAs can bind to the 3' untranslated region (UTR) of mRNAs, resulting in blockage of translation or mRNA degradation depending on the degree of complementarity between miRNA and mRNA (Ambros, 2004;Bartel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, DICER was found to play an essential role in thyroid function (20), hepatocyte survival, metabolism, tumor suppression (21) and in tumorigenesis (22). RNASEN (DROSHA) regulates cell proliferation and affects survival in esophageal cancer patients (23).…”
Section: Discussionmentioning
confidence: 99%